Stališče učiteljev do izkustvenega učenja in poučevanja predmeta spoznavanje okolja - Korban Črnjavič, Maja (Revija za elementarno izobraževanje, 2009)
According to Constructivism, experiential learning plays a great role in teaching because it produces many positive results. Not only does it increase the intellectual abilities of students, it also increases their inner motivation and desire to learn and discover new things. By learning experientially, we can achieve greater retention of the learned material, obtain a deeper understanding of the discussed material, develop cooperating skills and learn to connect theory with practice. With the recent renovation of the primary school system, experiential learning has become the basic starting-point in the subject Recognition of the Environment. In our research we wanted to find out the teachers' point of view towards experiential learning and teaching. We found that most of the teachers have a positive opinion about experiential learning and teaching, but they have noticed some negative aspects of it as well.
Keywords: vzgoja in izobraževanje; izkustveno učenje; spoznavanje okolja; osnovne šole